STUDIES ON FECUNDITY, SEX RATIO AND CROSSBREEDING IN DIFFERENT STRAINS OF GUPPY - PALAV, A. D.; BELSARE, S. G. (Journal of Indian Fisheries Association, 2015)
Studies on the fecundity, sex ratio and crossbreeding in different strains of the guppy Poecilia reticulata such as Butterfly I, Butterfly II and Cobra strains was carried out. The highest fecundity among Butterfly I strain was at the 5th breed while it was highest at the 6th and 8th breed among Butterfly II and Cobra strain respectively. The average male percentage was 39.88%, 43.39% and 45.02% among Butterfly I, Butterfly II and Cobra strains respectively. The crossbreeding of strains showed good results among crossbreeds of ButterflyQII ( ) X Cobra ( (1) and Butterfly I( ) X Cobra ( (1 ). The crossbreed among the Butterfly I( ) X Cobra ( 8) proved to be excellent from the point of view of more percentage, rapid growth, and brilliant body and finnage colouration.